2018
DOI: 10.3390/technologies6030071
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Evaluation on the Traffic State of an Urban Gated Community by Opening the Micro-Inter-Road Network

Abstract: The opening of a gated community to expand the micro-road network in an urban traffic system is an importance research topic related to urban congestion. To satisfy the demands of opening an early choosing case, this paper proposes a comprehensive selection framework on qualified communities and their appropriate opening times by describing the traffic state at the boundary road network accurately. The traffic entropy model and fuzzy c-means (FCM) method are used in this paper. In the framework, a new opening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…There are some different approaches on the impact and benefits of opening policies. For instance, Dong et al [ 30 ] approached the issue with a focus on its benefit for relieving the traffic burden. Their results showed that an opening policy will help decrease traffic congestion around gated community sites.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are some different approaches on the impact and benefits of opening policies. For instance, Dong et al [ 30 ] approached the issue with a focus on its benefit for relieving the traffic burden. Their results showed that an opening policy will help decrease traffic congestion around gated community sites.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To be more specific, GCs provide huge challenges to the traditional porosity and democracy of the street [21], which triggers the method of opening the gates and reconnecting the roads. Not only can openness erase the traffic congestion by expanding the micro-road network [33], it can also increase the overall connectivity and accessibility of the current road network and alleviate the urban traffic problem [34].…”
Section: Debates About Gated Communitiesmentioning
confidence: 99%
“…In essence, open blocks are an increase in the supply of transportation resources. Dong et al proposed that after opening the closed blocks, the density of the road network will be improved and the road area can increase, a result of which the road traffic capacity is naturally improved [23]. Zeng et al proposed that open blocks have a significant effect on the improvement of network performance and capacity and found that breaking "large blocks" and developing small-scale blocks can help to alleviate traffic pressure [24].…”
Section: A Literature Reviewmentioning
confidence: 99%